Inovasi Manajemen Melalui Pelatihan Pendaftaran Label BPOM dan Halal bagi Produk UMKM Kuliner Desa Legok Kabupaten Tangerang - Dewi, Cynthia Sari; Fianty, Melissa Indah; Saputri, Fahmy Rinanda (Jurnal Pengabdian UNDIKMA, 2024)
This community service activity aims to increase the knowledge and ability of MSMEs in Legok Village to register BPOM label products and halal labels as an effort to expand marketing, consumer confidence and business competitiveness. Methods of implementing this service uses training with lecture, demonstration and discussion stages. The evaluation instrument for this activity uses a questionnaire, which is then analyzed descriptively. The results of this service show that the business actors of the Legok Village Culinary MSMEs in Tangerang Regency have the ability and skills to register business products with BPOM and halal labels. BPOM and Halal labels can be utilized as product innovation in increasing business competitiveness.